2013
DOI: 10.4103/1596-3519.112402
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and pattern of tooth mortality in a Nigerian Urban teaching hospital

Abstract: Tooth mortality in Nigerians is significantly associated with dental caries and its sequelae especially in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
9
26
2
1
Order By: Relevance
“…Over the years, various authors have reported that dental caries is the major cause of tooth loss in developed countries . In this study, as in previous studies from Nigeria, periodontal disease was the major cause of tooth loss, possibly because of traditions and beliefs from the use of chewing sticks that present with gingivitis and periodontitis . Therefore, the public should be educated on the negative impact of such traditions and beliefs on oral health.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Over the years, various authors have reported that dental caries is the major cause of tooth loss in developed countries . In this study, as in previous studies from Nigeria, periodontal disease was the major cause of tooth loss, possibly because of traditions and beliefs from the use of chewing sticks that present with gingivitis and periodontitis . Therefore, the public should be educated on the negative impact of such traditions and beliefs on oral health.…”
Section: Discussionsupporting
confidence: 58%
“…The main cause of tooth loss in developed countries is the sequela of dental caries and periodontal disease with other factors also implicated . Periodontal disease is a major cause of tooth loss in elders in Nigeria . However, tooth loss due to dental caries has increased in Nigeria due to dietary changes, poor oral hygiene, attitude and practice to oral health …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The reasons for extraction included pain (34.6%), a large cavity (5.6%), periodontal problems (6.0%), and endodontic problems (3.2%). 9 The younger population (5-12 years old) seemed to experience extractions mostly because of caries (64.3%) and dental trauma (43.0%). 9 The younger population (5-12 years old) seemed to experience extractions mostly because of caries (64.3%) and dental trauma (43.0%).…”
Section: Tooth Loss and Miss Ing Tee Thmentioning
confidence: 99%
“…5 Another study reporting on missing teeth in 14-to 89-year olds found caries accounted for 86.2% of extractions, periodontal disease accounted for 6.6% of extractions, and trauma for 3.9% of extractions. 9 The younger population (5-12 years old) seemed to experience extractions mostly because of caries (64.3%) and dental trauma (43.0%). 4 European and US studies estimate periodontitis to affect 31%-76% of individuals.…”
Section: Tooth Loss and Miss Ing Tee Thmentioning
confidence: 99%